Intrinsic Enantioselectivity of Natural Polynucleotides Modulated by Copper Ions. Issue 4 (9th February 2015) - Fu, Yan; Chen, Xiongfei; Zhang, Jinli; Li, Wei
Abstract Natural polynucleotides including Micrococcus lysodeikticus and calf thymus DNA exhibit enantioselective recognition to S‐ofloxacin regulated by Cu2+. This is the first report that ofloxacin and Cu2+ have cooperative effects on the local distortions of polynucleotides. At the [Cu2+]/[base] ratio of 0.1, S‐ofloxacin is more liable to induce the locally distorted structures of polynucleotides, of which the association constant of S‐ofloxacin toward DNA‐Cu(II) is three times higher than that of the R‐enantiomer. The apparent increase of adsorption capability and cooperativity, as well as the change of adsorption mechanism were detected in the adsorption of ofloxacin enantiomers on polynucleotides upon Cu(II)‐coordination. This study not only discloses the effect of the chiral drug on the structural transition of long double‐stranded DNA, but provides fundamental data to develop a novel enantioseparation method based on natural polynucleotides. Chirality 27:306‐313, 2015. © 2015 Wiley Periodicals, Inc.